2007
DOI: 10.1038/labinvest.3700531
|View full text |Cite
|
Sign up to set email alerts
|

High-fidelity DNA histograms in neoplastic progression in Barrett's esophagus

Abstract: This study describes the high-fidelity DNA histograms in different stages of neoplastic progression to Barrett's adenocarcinoma (BAC). High-fidelity DNA histograms were obtained with image cytometry on sections, and were classified based on DNA index values of the peaks into diploid, mild aneuploid, moderate aneuploid and severe aneuploid. Heterogeneity index (HI) representing cells with different DNA content and the 5N exceeding cell fraction were determined. One hundred and eighty-seven cases, including 34 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 19 publications
5
51
0
Order By: Relevance
“…However, by virtue of identifying a small number of abnormal nuclei from the area of interest, image cytometry may identify much higher rates of rare aneuploid cells that are not detected by flow cytometry 41. For instance, Yu et al reported that more than two-thirds of BO without dysplasia (69%) and LGD (82%) samples have aneuploid populations 49. Similarly, Fang et al demonstrated that up to 13% of BO without dysplasia and 60% of LGD samples showed DNA content abnormality 50.…”
Section: Discussionmentioning
confidence: 99%
“…However, by virtue of identifying a small number of abnormal nuclei from the area of interest, image cytometry may identify much higher rates of rare aneuploid cells that are not detected by flow cytometry 41. For instance, Yu et al reported that more than two-thirds of BO without dysplasia (69%) and LGD (82%) samples have aneuploid populations 49. Similarly, Fang et al demonstrated that up to 13% of BO without dysplasia and 60% of LGD samples showed DNA content abnormality 50.…”
Section: Discussionmentioning
confidence: 99%
“…This has been reported previously and attributed to the intrinsic characteristics of performing DNA ploidy analysis using thin tissue sections. 43,64 Thick tissue sections (e.g., 410 μm) create difficulty in nuclei segmentation, especially in situations of touching and overlapping nuclei. Therefore, biased sampling error could happen where smaller and isolated nuclei are preferred.…”
Section: Discussionmentioning
confidence: 99%
“…18,38,39 Nonetheless, the majority of other studies are still focusing on the well-established DNA density measurements using tissue sections (e.g., 3-7 μm), especially the use of the commercially available ACIS system (Automated Cellular Imaging System, Dako, Denmark) from a field of view (FoV) of tissue sections. [40][41][42][43][44] Under a microscope at × 40 magnification, a FoV is digitally captured followed by image analysis to locate nuclei and to measure the integrated optical density (IOD) for each nucleus. DNA content histogram for FoV can then be constructed.…”
mentioning
confidence: 99%
“…In some studies, aneuploidy heralds an aggressive genotype [42,[48][49][50]. DNA content abnormalities, similar to those found in LGD, occur in the basal portions of crypts in ND epithelium [51].…”
Section: Pathologic and Molecular Features Of Barrett's Esophagusmentioning
confidence: 95%